Interventions to Increase In-Patient Visits at Gambiran Hospital, Kediri City, during The Covid- 19 Pandemic - Trianike Nor Aini; Mas Roro Dyah Ayu; Iman Gautama; Galih Duta Prihadi; Jumita Dos Santos G (Ridwan Institute, 2022)
Currently, hospitals must contend with global competition in various health sectors. The public's demand for health services increases annually. The community requires prompt, accurate, and high-quality services. With the increasing number of patients and the limitations of government hospitals, there are frequently public complaints about hospital services. In addition, a patient's interest in receiving services at a hospital is influenced by his or her satisfaction with those services, so if hospital services are subpar, this will have an effect on the number of hospital visits in the era of the COVID-19 pandemic. The purpose of this study is to provide an overview of efforts to increase inpatient visits at Gambiran Hospital. The method employed is qualitative surveying. The results of the study indicate that several appropriate strategies are required to address the various problems that have been identified, particularly during the current pandemic, including the need to increase the capacity of officers to be able to provide education to patients, along with superior human resources to market through media, which is required by society today in order to instill community confidence in the safety of care at the Gambiran Hospital.